Explaining the Dimensions of Spiritual Health of Iranian Children: Conventional Content Analysis - Soolmaz Moosavi; Hanieh Gholamnejad; Maryam Safara (Gonabad University of Medical Sciences, 2024)
Background: Spiritual health is part of the general concept of child health. Considering the effects of spiritual health on the growth and development of children, it is necessary to understand the concept of spiritual health and its dimensions in children. Accordingly, this study explains the dimensions of children's spiritual health.  Methods: This qualitative study was conducted using conventional content analysis. The data was collected through semi-structured interviews with 17 children and 9 researchers and specialists in the field of children's mental health. Interviews were conducted with an average duration of 30 min. Results: Dimensions of children's spiritual health with two themes of balanced relationship in 4 categories of relationship with God, relationship with self, relationship with others, and relationship with the environment, and the theme of relationship transcendence in 2 categories of transcendent behaviors and love of God were explained.  Conclusion: Regardless of other developmental principles that follow the rule of maturity, the balanced relationship of spiritual health and the relationship transcendence of spiritual health in children did not follow the rule of maturity, and due to the innateness of the themes of balanced relationship and relationship transcendence of spiritual health. These characteristics have existed in children since childhood, regardless of any religious-spiritual measures within the family, and their spiritual health potential has been realized from their potential state.